Impact of Ventilator-associated Pneumonia on Cerebrospinal Fluid Inflammation During Immunosuppression After Subarachnoid Hemorrhage: A Pilot Study. Issue 1 (16th January 2022) - Coelembier, Clément; Venet, Fabienne; Demaret, Julie; Viel, Sébastien; Lehot, Jean-Jacques; Dailler, Frédéric; Monneret, Guillaume; Lukaszewicz, Anne-Claire
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: Brain injuries can cause systemic immunosuppression, which in turn can lead to infections that adversely affect the injured brain and worsen clinical outcomes. This study aimed to investigate whether systemic infection, such as ventilator-associated pneumonia (VAP), induce intracranial inflammation in patients with subarachnoid hemorrhage (SAH). Methods: This prospective, observational study included 16 adults with SAH treated in the neuro-intensive care unit. Three paired cerebrospinal fluid samples (obtained from an external ventricular drain) and peripheral blood samples were obtained on days 1 to 3, 4 to 5, and 6 to 7 after SAH onset. Cell counts, cell phenotypes (monocyte HLA-DR, T regulatory cells, lymphocytes, and neutrophils), and inflammatory mediator levels were monitored. Results: Six patients developed VAP in the context of systemic immunosuppression demonstrated by a reduction in monocyte HLA-DR expression, lymphopenia, increased percentages of circulating T regulatory cells, and increased proportions of immature and immunosuppressive neutrophil subsets. During VAP, there was de novo recruitment of leukocytes into the cerebrospinal fluid, preferentially neutrophils, which exacerbated intracranial inflammation. Conclusions: VAP increased intracranial inflammatory responses in patients with SAH despite the occurrence of systemic immunosuppression. A better understanding of cell trafficking and their pleiotropic functions in brain injury is needed to define the optimal strategies for preventing infections in patients with SAH.